Impact of BRCA mutations and hormone receptor status on reproductive potential in breast cancer patients undergoing fertility preservation. (4th March 2022) - Kim, Sung Woo; Kim, Tae Hee; Han, Ji Yeon; Kim, Seul Ki; Lee, Jung Ryeol; Jee, ung Chul; Suh, Chang Suk; Kim, Seok Hyun
Abstract: Objective: To identify whether the BRCA mutations and hormone receptor status affect the ovarian reserve and ovarian stimulation outcomes in breast cancer patients undergoing fertility preservation. Methods: A total of 117 women diagnosed with breast cancer who were referred to the fertility preservation clinics at Seoul National University Bundang Hospital and Seoul National University Hospital between September 2012 and July 2019 undergone ovarian stimulation for oocyte retrieval. Basal characteristics including age, BMI, basal AMH, basal FSH, and fertility preservation outcomes such as the number of retrieved oocytes and mature oocytes were compared retrospectively. Results: BRCA1 mutation was noted in 25 women, and BRCA2 mutation was observed in 35 women. Positive estrogen receptor status was noted in 87 women, and positive progesterone receptor status was noted in 69 women. HER2 was positive in 55 women, and 19 women were diagnosed with triple-negative breast cancers. The number of total oocytes retrieved was lower in patients with BRCA mutation (8.3 ± 5.4 vs. 15.3 ± 8.7, p = .002). The number of mature oocytes retrieved was also lower in BRCA carriers (4.7 ± 4.2 vs. 8.7 ± 7.9, p = .025). Triple-negative breast cancer (TNBC) patients were younger than non-TNBC patients (30.3 ± 4.8 vs. 33.9 ± 5.0, p = .007). The rate of mature oocyte rate was higher in TNBC patients (68.6%±20.6 vs. 52.5%±29.7, p = .037). Conclusions: Our study demonstrated that BRCA carriers with breast cancer had comparable ovarian reserve to non-carriers but the response to ovarian stimulation was lower. We also observed that oocyte maturity was higher in TNBC patients, however age might be a confounding factor of this result.